Rock magnetic properties as proxy indicators of characteristic periodicities in Holocene aeolian sediments (Arturo Dune, Tierra del Fuego, Argentina). (June 2022) - Orgeira, M.J.; Achaga, R.; Cappellotto, L.; Gogorza, C.; Coronato, A.; Ponce, J.F.; Velasco Herrera, V.M.
Abstract: The objective of this contribution is to distinguish characteristic wind speed periodicities from a roughly 19 m-thick profile of Arturo Dune (Tierra del Fuego, Argentina), which contains eight interbedded paleosoils. The results include different magnetic properties and ratios measured in 29 aeolian sediment samples. These properties are coercive force (HC ), saturation magnetization (MS ), low-frequency (470 Hz) magnetic susceptibilities (kLF ), anhysteretic remanent magnetization (ARM), among others. The statistical analysis of the variations in the magnetic properties of detrital minerals over time could indirectly indicate prevailing periodicities of the wind rate during the studied interval. The power spectral analysis was done using wavelets and multiple cross wavelets. The analysis by wavelets made it possible to distinguish periodicities in the variations of climatic parameters. A main periodicity of 2824 years was obtained in the different wavelet and multiple cross wavelet analyses of the magnetic parameters. By adding the δ 18 O series from the deep South Atlantic Ocean to the spectral power analysis, a periodicity of around 3000 years was also obtained. These periodicities could be related to a fundamental solar mode, with a periodicity of 2300 years (Hallstattzeit cycle). Still, they are not conclusive as solid empirical evidence to support sun-climate relationships on a series of millennial suborbital time scales. Highlights: Wind speed periodicity search in aeolian sediments (Arturo Dune, Tierra del Fuego). We used wavelet analysis to find periodicities in climatic parameters variations. We found a periodicity of around 3000 yrs in magnetic parameters and δ 18 O series. The periodicity found could be related with a solar cycle of 2300 years.